The cytokine GDF15 signals through a population of brainstem cholecystokinin neurons to mediate anorectic signalling - Amy A Worth; Rosemary Shoop; Katie Tye; Claire H Feetham; Giuseppe D'Agostino; Garron T Dodd; Frank Reimann; Fiona M Gribble; Emily C Beebe; James D Dunbar; Jesline T Alexander-Chacko; Dana K Sindelar; et al. (eLife, 2020)
The cytokine, GDF15, is produced in pathological states which cause cellular stress, including cancer. When over expressed, it causes dramatic weight reduction, suggesting a role in disease-related anorexia. Here, we demonstrate that the GDF15 receptor, GFRAL, is located in a subset of cholecystokinin neurons which span the area postrema and the nucleus of the tractus solitarius of the mouse. GDF15 activates GFRALAP/NTS neurons and supports conditioned taste and place aversions, while the anorexia it causes can be blocked by a monoclonal antibody directed at GFRAL or by disrupting CCK neuronal signalling. The cancer-therapeutic drug, cisplatin, induces the release of GDF15 and activates GFRALAP/NTS neurons, as well as causing significant reductions in food intake and body weight in mice. These metabolic effects of cisplatin are abolished by pre-treatment with the GFRAL monoclonal antibody. Our results suggest that GFRAL neutralising antibodies or antagonists may provide a co-treatment opportunity for patients undergoing chemotherapy.